A study of the effect of grinding environment on the flotation of two copper sulphide ores. (15th June 2018) - Liu, J.; Long, Han; Corin, K.C.; O'Connor, C.T.
Highlights: Influence of grinding on flotation of copper sulphide ores is investigated by tests in laboratory. Milling procedure affects concentrations of Cu and Fe in the pulp and flotation results. The effect of grinding condition on the flotation result is ore-dependent. Hypothesis for the test results based on mineralogy, pulp chemistry and mineral surface property. Abstract: It is well known that different milling procedures may result in different flotation responses. In the present study, the effect of various grinding conditions such as wet or dry grinding and addition of lime to the mill compared to the flotation cell on the flotation of two different copper sulphide ores was investigated. The milling was carried out in a Magotteaux Mill which enables reagent addition during milling as well as the monitoring of changes in parameters such as pH, Eh and DO during milling. The paper will present grade and recovery results obtained after the different milling procedures. After wet milling, the ores yielded different concentrations of Cu and Fe in the pulp and also significantly different recoveries. Dry grinding affected the behaviour of the ores differently. Proposals are made to explain the results by reference to the mineralogical properties of the two ores.